Pengaruh Media Visual Terhadap Keaktifan Belajar Siswa Pendidikan Agama Kristen Kelas V SD Negeri 10 Hutagalung Tahun Pembelajaran 2022/2023 - Sutri Natalia Nababan; Boho Pardede; Dame Taruli Simamora; Johari Manik; Taripar Aripin Samosir (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
This research aims to find out the influence of visual media on the learning activity of Christian religious education students in class V at SD Negeri 10 Hutagalung for the 2022/2023 academic year. This research uses quantitative descriptive statistical methods, with a population of 30 people and a sample of 30 people. Data was collected using a closed questionnaire instrument of 30 items, namely 17 items for variable X and 13 for variable Y which was tested on 30 students who were not research respondents. The results of data analysis show that there is a positive and significant influence of visual media on the learning activity of class V Christian religious education students at SD Negeri 10 Hutagalung, Harian District, Samosir Regency for the 2022/2023 Academic Year: a) the positive relationship test is obtained from (r_xy) = 0.748 > r_ (table (α=0.05,n=30))= 0.361. b. Testing a significant relationship obtained a t_(calculated) value of 5.978, it is known that t_(table) in α=0.05 n-2=30-2=28 is 1.701. 2) Influence test: Regression equation test Y ̂= 13.40+ 0.50x. b) Regression determination test (r^2)= 55.9%. 3) Test the hypothesis using the F test, obtained f_count > f_(table ) namely 35.04 > 4.24. Thus Ha is accepted and H0 is rejected.